The Role of Artificial Intelligence in Improving the Efficiency of the Company's Supply Chain - Husein, Muh; Rajagukguk, Jenni Ria; Putranto, Kartiko Eko (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2024)
The development of technology, especially in the era of Industry 4.0, has significantly impacted various sectors, including supply chain management. Artificial Intelligence (AI), one of the leading technologies in Industry 4.0, has excellent potential to improve the efficiency and effectiveness of the supply chain. This study aims to identify the relationship between AI and the concept of supply chain management and analyze the practice of using AI to improve supply chain efficiency at PT. Pelita Media Nusantara. Using a descriptive-analytical method, this study examines various relevant literature and data. The results of the study indicate that the application of AI at PT. Pelita Media Nusantara has increased the supply chain's visibility, accuracy, and responsiveness. Implementing big data analytics, IoT sensors, and AI-based predictive systems allows companies to optimize procurement, production, and distribution processes. This case study also reveals that complex technology integration and the need for skilled human resources are the main challenges in implementing AI. This study provides important insights for academics and practitioners in developing more effective and efficient AI-based supply chain management strategies.